VD_FINDINFO AP / 2009 / 35 vom 16. Oktober 2007 - VD Tribunal cantonal (2007)
TÉMOIN, SOCIÉTÉ SIMPLE, CONSORITÉ, INTERPRÉTATIONSENS GÉNÉRAL, ENRICHISSEMENT ILLÉGITIME, PRESCRIPTION | 18 CO, 530 CO, 67 al. 1 CO, 296 CPC, 297 CPC